Creation of the own family: challenges for the values forming on youngsters - Katia María Pérez Pacheco; Teresa de la C. Díaz Domínguez; Anselmo Vázquez Vázquez; Alina María Rivero Brito (Revista MENDIVE, 2013)
The study suggests to characterize the preparation of the young university student for the creation of his own family in a process of relation with the Values forming process from the teacher’s, directors and specialists perspectives. The methods used: General Dialectic; Historical Logic; observation, interview, survey and focused group. A sample is composed by 15 teachers, 10 directors and 8 specialists. As results: there is no background knowldge in preparing the young university student for creating his own family, or a correlate explicit relation with the formation of values on the documents analyzed. They haven ́t been trained didactically or pedagogically to work with this matters and considered relevant to assign a formative space to this sphere.